REFERENCE AND FUNCTION OF CURSING IN KAILI - Deni Karsana (Metalingua: Jurnal Penelitian Bahasa, 2015)
CURSING is a verbal expression which we encounter in daily life. This writing aimsat describing the cursing in Kaili language using descriptive qualitative method.The result shows that there are two kinds of cursing in Kaili language. Firstly,the cursing that is based on the references, namely a) situations, b) animals, c)things, d) body parts, e) kinship, f) ghosts, g) activities, h) appellations, and i)phatic words. Secondly, based on its functions the cursing in Kaili language canbe used to express anger, dejection, disappointment, astonishment, contempt orharassment, sense of humor, and warning.